Impacts of model resolution on responses of western North Pacific tropical cyclones to ENSO in the HighResMIP-PRIMAVERA ensemble - Liu, Jingchan; Yuan, Chaoxia; Luo, Jing-Jia (Frontiers in Earth Science, 2023)
The El Niño/Southern Oscillation (ENSO) is the major driver of interannual variations of the western North Pacific (WNP) tropical cyclones (TCs). Realistic reproduction of ENSO-WNPTC teleconnection in coupled models (CGCMs) is thus crucial for improved seasonal-to-interannual prediction of WNPTC activity. Here, basing on the outputs of six pairs of high-resolution (HR) and low-resolution (LR) CGCMs participating the HighResMIP-PRIMAVERA project, we showed that the HR models outperform the LR ones in reproducing the observed increase of TC genesis in the southeastern WNP but the decrease in the northwestern WNP in the developing years of El Niño. The better performance of HR than LR models is on one hand due to the generally increased frequency and variability of TCs in the HR models. On the other hand, the teleconnection of El Niño to the WNP shows a dipole circulation difference between the HR and LR models with an anomalous cyclone in the southeastern WNP and anticyclone in the northwestern WNP, which enhances the dipole TC genesis anomalies in the HR compared to the LR models. The teleconnection difference stems from the westward shift of the ENSO-related SST and convection anomalies in the tropical Pacific in the HR compared to the LR models, which may be ultimately linked to the reduced cold tongue biases in the HR models.